Chemical and physical activation of natural pyrite as potential inorganic pigment material - Iqbal, Rendy Muhamad; Simarmata, Sari Namarito; Sinaga, Tiara Cristy; Simanjutak, Elfrida Roulina; Putra, Riandy; Khaerudini, Deni Shidqi (Konversi, 2024)
Pyrite is one of the minerals in Borneo Island. It has a disadvantage for soil quality due to its acidity properties. One of the main components of pyrite is iron, which promises to be utilized as an inorganic pigment. This research aims to transform pyrite into red-brown pigment material-based iron oxide. Pyrite mineral transformation through chemical and physical activation, followed by pigment characterization using XRF, XRD, FTIR, and FE-SEM. Based on the XRF result, the highest component is Fe, with a percentage up to 42%. This data is also suitable with an iron oxide phase from the diffractogram of pigment, followed by silica and alumina structure. The heating process successfully changed the color materials from gold to red-brown. Then, the molecular vibration of Fe–O also appears on FTIR spectra at a wavenumber of 483 cm-1 and T–O–T bending at 994 cm-1. Moreover, morphological observation exhibits the aggregation of particles and distribution of iron element spread on the overall area pigment. The color transformation into red-brown pigment can be obtained by pyrite processing into potential inorganic pigment material.